2017
DOI: 10.4103/pm.pm_490_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antidiabetic properties of S-1708 mulberry variety

Abstract: Background:Diabetes is a metabolic disease prevalent worldwide in all age group of people. The source of diabetes is due to an oxidation process that can produce free radicals. An increase in oxidative free radicals in the body is reported to be one of the several causes of diabetes. The best remedy to combat oxidative stress is the use of antioxidants, which inhibit and scavenge free radicals.Aim:This study has been undertaken to evaluate the antioxidant activity and antidiabetic effect of mulberry leaf extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Consistent with our results, previous studies have reported that anthocyanin decreases SGOT and SGPT in diabetic mice ( Alli et al, 2017 ; Ranjan et al, 2017 ). For example, anthocyanin in the form of cyanidin 3-caffeoyl- p -hydroxybenzoylsophoroside-5-glucoside inhibited hepatic glucose secretion in hyperglycemic mice.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with our results, previous studies have reported that anthocyanin decreases SGOT and SGPT in diabetic mice ( Alli et al, 2017 ; Ranjan et al, 2017 ). For example, anthocyanin in the form of cyanidin 3-caffeoyl- p -hydroxybenzoylsophoroside-5-glucoside inhibited hepatic glucose secretion in hyperglycemic mice.…”
Section: Resultssupporting
confidence: 93%
“…Recent studies have reported several pharmacological effects of mulberry leaves, including blood pressure stabilization [3], cholesterol reduction [4], thrombolysis [5], antioxidation [6], and antiobesity [7–9]. In particular, a number of human [10, 11] or animals [12–16] studies have reported to confirm the antidiabetic activity of mulberry extract by regulating blood glucose level.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al found that mulberry extract had a protective effect on the increase of ROS and vascular endothelial damage caused by high sugar and high fat (Bai et al, 2021). Ranjan et al found that mulberry extract could achieve its antioxidant effect by reducing the activities of catalase, serum glutamic oxaloacetic transaminase, and serum glutamic pyruvic transaminase in mice used as diabetes models (Ranjan et al, 2017). This research found that the mulberry branch and mulberry leaf had highly similar bioactivities, and the antioxidant and antiapoptotic effects of the mulberry branch were even greater than the mulberry leaf (Figures 2B and 3B).…”
Section: Resultsmentioning
confidence: 99%